Eksistensi dan Dinamika Jamaah Rifa’iyah di Desa Sukawera, Kertasemaya, Indramayu Tahun 2005-2020: Aktivitas Keagamaan dan Pendiidkan - Khanna Riyatul Maula; Ahmad Faiz Rofi'i; Samudra Eka Cipta; Andri Nurjaman (UIN Sunan Gunung Djati Bandung, 2025)
This article examines the existence and dynamics of the Rifa’iyah organization in Sukawera Village, Kertasemaya Subdistrict, Indramayu Regency, during the period of 2005–2020 by applying the four stages of the historical method: heuristics, criticism, interpretation, and historiography. This study is significant considering that the existence of Rifa’iyah in Sukawera has received limited attention in local historical literature, despite the fact that this organization is an Islamic group that has endured various challenges from the colonial era through the Reform era. Originating as a cultural movement, Rifa’iyah has successfully maintained its existence through religious activities centered on the Tarjumah recitations and the development of educational institutions. These two activities serve as the main pillars in sustaining the continuity of the movement as well as representing the organization’s adaptation to social dynamics and changing times.